ANALISIS KOMPETENSI ICT GURU SEKOLAH MENENGAH ATAS - Putri Cinndy Shylvia; Agus Setiawan; Rama Wijaya Abdul Rozak (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the competence of high school teachers in using Information and Communication Technology (ICT) in learning. This study examines the intensity of the use of digital devices, mastery of computer applications, constraints faced by teachers, and sources of information obtained to use ICT in learning. The research method used was a survey with a questionnaire distributed to 70 high school teachers in Bandung Regency. The results showed that although teachers are familiar with basic applications such as word processing and presentation, mastery of interactive learning applications is still low. The obstacles faced include limited infrastructure, lack of relevant training, and difficulty integrating ICT into learning effectively. This study recommends the need for infrastructure improvement, continuous training, and mentoring for teachers to optimize the use of ICT in learning.